If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -116 = 4x + -14 Reorder the terms: -116 + 10x = 4x + -14 Reorder the terms: -116 + 10x = -14 + 4x Solving -116 + 10x = -14 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -116 + 10x + -4x = -14 + 4x + -4x Combine like terms: 10x + -4x = 6x -116 + 6x = -14 + 4x + -4x Combine like terms: 4x + -4x = 0 -116 + 6x = -14 + 0 -116 + 6x = -14 Add '116' to each side of the equation. -116 + 116 + 6x = -14 + 116 Combine like terms: -116 + 116 = 0 0 + 6x = -14 + 116 6x = -14 + 116 Combine like terms: -14 + 116 = 102 6x = 102 Divide each side by '6'. x = 17 Simplifying x = 17
| x/26=10 | | (100+x)+x=110 | | 6.75+2.25x= | | -x+5=x+4 | | 4+35x=28x+8 | | 2y^2=9-4y | | 12+8q=15+7q | | 2(x+1)-3=3x-4 | | a=(12.5)(14.75) | | 72+2x+x=180 | | 2500+300=5000 | | -9-4x=-53x | | 6x-10=4x+4 | | 9y+3=5y+12 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 13-6x=5-7x | | 15x^2-19x=10 | | b+52=64 | | 6x+6=-54-4x | | 3(g+5)=36 | | (7-4i)(5+8i)= | | 12x+1=2x+3 | | 5g+g=12 | | 5+-2x=3x+1 | | 2(x+11)=0 | | 34=6-5x | | 19=9x+4-6x | | 5y+3(y-8)=5(y+1)-3 | | 2(x^2+6)+(2x-9)*2x= |